2003
DOI: 10.1074/jbc.x200003200
|View full text |Cite
|
Sign up to set email alerts
|

Happily at Work

Abstract: It is a great privilege to be asked for a "Reflections" essay; I admire those prepared by my predecessors. My teachers were less prestigious than Arthur Kornberg's (1), and there was no single major theme in my research as was the case with several previous contributors to this series. Instead we studied a wide variety of metabolic phenomena that I have described in a summary of my first 50 years of biochemical research (2).Our findings included a treatment for selenium poisoning in livestock (undergraduate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 82 publications
0
24
0
Order By: Relevance
“…DHEA, pregnenolone and 5-Adiol are readily hydroxylated at C7 (Akwa et al, 1992;Lathe, 2002;Lardy, 2003). Moreover, these 7 -11 hydroxy-and 7 -hydroxy-steroids can be oxidized to 7-oxo-steroids [ Figure 4].…”
Section: A Paradox the Er And Not The Pr Is Most Ancient: What Was Tmentioning
confidence: 99%
“…DHEA, pregnenolone and 5-Adiol are readily hydroxylated at C7 (Akwa et al, 1992;Lathe, 2002;Lardy, 2003). Moreover, these 7 -11 hydroxy-and 7 -hydroxy-steroids can be oxidized to 7-oxo-steroids [ Figure 4].…”
Section: A Paradox the Er And Not The Pr Is Most Ancient: What Was Tmentioning
confidence: 99%
“…Despite early statements of Meyerhof et al (3) that the reaction was irreversible, Lardy and Ziegler (4) experimentally showed in rat muscle extracts its reversibility in 1945 from the exchange of 32 P between P-enolpyruvate and ATP. These workers further showed that P-enolpyruvate could be synthesized directly from pyruvate in a system where ATP was constantly being regenerated and that the rate of reaction increased with increasing potassium concentration (4,5). The reversibility of the reaction in muscle extracts was subsequently shown by Krimsky (6) and McQuate and Utter (7) in 1959 and again by Dyson et al (8) in 1975.…”
Section: ؊mentioning
confidence: 99%
“…However, the physiological role, the mechanism by which they prevent intracellular Ca 2C increase and the signaling pathways that they modulate are still unknown. In addition, although some of them have trypsin inhibitor activity (Lardy 2003), whether their caltrin function is related to its trypsin inhibitory activity remains to be demonstrated. Therefore, our first aim was to study the possible interaction between SPINK3 Ca 2C uptake inhibition and the levels of NO in mouse sperm during capacitation.…”
Section: Introductionmentioning
confidence: 99%